Examining the influence of trust and perceived risk on customers intention to use NFC mobile payment system - Mahmaod Alrawad; Abdalwali Lutfi; Mohammed Amin Almaiah; Ibrahim A. Elshaer (Journal of Open Innovation: Technology, Market and Complexity, 2023)
The current study investigates how perceived risks and trust factors affect customers' intentions to use mobile payment applications that utilize near-field communication (NFC) technology. The author created a conceptual model that includes five elements: intention to use, perceived risk, process-based trust, characteristics-based trust, and institution-based trust. Data was gathered through an online survey of 469 participants and analyzed using partial least squares structural equation modeling techniques. The results indicate that only three of the four tested constructs significantly impact customers' decisions to use NFC mobile payments: perceived risk, process-based trust, and characteristics-based trust. Additionally, the study found that age and gender do not play a significant role in influencing the model constructs; therefore, the findings of current research highlight how perceived risk and trust have a pivotal role of in shaping customers' intention to use NFC as a mobile payment and how trust can substantially mitigate customers' perceived risk. Hence, this knowledge can aid in developing effective strategies for promoting mobile payment adoption among consumers.